Crystal structure of 3β-[5-phenyl-(2E,4E)-penta-2,4-dienoyloxy]- olean-12-ene, C41H58O2, from Peltastes peltatus - Humberto M. M. S.; Da Silva V. R. M.; Sant’Ana A. E. G.; De Simone C. A.; Malta V. R. S.; Pereira M. A. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C41H58O2, monoclinic, C121 (no. 5), a = 25.573(3) Å, b = 10.453(1) Å, c = 14.159(2) Å, β = 113.674(8)°, V = 3466.3 Å3, Z = 4, Rgt(F) = 0.069, wRref(F2) = 0.180, T = 120 K.